2019
DOI: 10.1080/21580103.2018.1530151
|View full text |Cite
|
Sign up to set email alerts
|

DBH growth for three years after thinning on even-agedPinus koraiensisandLarix kaempferiplantations in South Korea

Abstract: This study was conducted to determine the effects of different thinning intensities on the DBH growth of Pinus koraiensis and Larix kaempferi trees. Permanent monitoring plots were installed in 26 P. koraiensis plantations and 36 L. kaempferi plantations in 2012 and 2014, respectively. To evaluate the effect of thinning intensity, each plot consisted of three square or rectangular plots; control or non-thinned, light thinning, in which 20% of the total basal area was removed, and heavy thinning, in which 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Larix kaempferi (Kim et al, 2016), Eucalyptus grandis hybrid (Filho et al, 2018), Eucalyptus camaldulensis (Aiso-Sanada et al, 2019), and Pinus koraiensis (Seo et al, 2019). In teak, previous studies reported that thinning and pruning treatments significantly increase the radial growth of the remaining stands (Budiadi et al, 2017;Kanninen et al, 2004;Víquez and Pérez, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Larix kaempferi (Kim et al, 2016), Eucalyptus grandis hybrid (Filho et al, 2018), Eucalyptus camaldulensis (Aiso-Sanada et al, 2019), and Pinus koraiensis (Seo et al, 2019). In teak, previous studies reported that thinning and pruning treatments significantly increase the radial growth of the remaining stands (Budiadi et al, 2017;Kanninen et al, 2004;Víquez and Pérez, 2005).…”
Section: Introductionmentioning
confidence: 98%